Deep-Sea asteroids (Echinodermata; Asteroidea) from the Galician Bank (North Atlantic Ocean) - García-Guillén, Laura M.; Macías-Ramírez, Aurora; Ríos, Pilar; Manjóncabeza, M. Eugenia (Zootaxa, 2023)
The Galician Bank (GB) is a seamount located 180 km away from the Galician coast (Northwest Spain), in the Northeast Atlantic Ocean. The summit occurs at a depth between 650 and 1500 m with the maximum depth reaching 4000 m (the abyssal bottom). The water masses, twists, eddies, and geomorphology favour the retention of nutrients and larvae, thus, being an area rich in nutrients. It is a hotspot of biodiversity and an important place for benthic communities. This study aims to inventory and review the asteroid fauna collected during the LIFE+INDEMARES project in GB, compare the new findings with previous studies Official Spanish Checklist (IEEM: “Inventario Español de Especies Marinas”, Manjón-Cabeza et al. 2017, 2020) and update our knowledge of the diversity and distribution of known species. In this study a total of 272 asteroid specimens belonging to 19 species were found at 45 stations in depths between 765–1764 m, as part of the LIFE+INDEMARES-Galician Bank (2010–2011) surveys. The most frequently encountered species were Plinthaster dentatus (Perrier, 1884), Peltaster placenta (Müller & Troschel, 1842) and Henricia caudani (Koehler, 1895). Circeaster americanus (A.H. Clark, 1916) and Hymenaster giboryi (Perrier, 1894) are new observations from this area. For several species, including Henricia caudani, Pedicellaster typicus M. Sars, 1861, Podosphaeraster thalassae Cherbonnier, 1970 and Hymenaster giboryi known bathymetric range has been extended.